Double Exile: Jean Rhys's Wide Sargasso Sea (Journal of the College of Education for Women, 2019)
The problems of cultural displacement and a shaky sense of one's own identityhave been the main concern of the twentieth century Caribbean writer, Jean Rhys. Asa white Creole writer living in England, Rhys attempts to capture the ambivalence ofwhat it means to be caught between two cultures and never able to identify fully withany one .Born to a Welsh father and a Creole(white West Indian) mother on the islandof Dominica in the West Indies, Jean Rhys was white but not English, West Indian butnot black. Her sense of belonging to the West Indies was necessarily charged withawareness of being part of another culture. Thus, the ambiguity of being aninsider/outsider in both the metropolis, England, and the colony, West Indies, shapedRhys' world, resulting in her sense of exile and marginalityThe purpose of the research is to examine how Rhys gives the same sense ofexile and marginality to Antoinette Cosway, the heroine of her 1966 novel WideSargasso Sea, through whom she reflects the unique experience of dislocation of thewhite Creole woman.